A darkside of academia: a study of bullying, its prevalence, causes and perpetrators in an academic setting - Björklund, Christina; Jensen, Irene (Frontiers in Education, 2025)
ObjectiveBullying in academia, often characterised by insulting comments, persistent criticism, personal or even physical abuse, and threats, is a persistent issue, with prevalence varying across countries and institutions. Hierarchical structures within higher education institutions create power dynamics that may exacerbate the prevalence and impact of bullying. This study aims to examine the prevalence and causes of bullying among faculty in a Swedish medical university over time, identifying common perpetrators and relationships between targets and perpetrators.MethodsData were derived from a longitudinal work environment survey conducted at a Swedish medical university, with two data collection points: Time 1 (T1) in 2009 and Time 2 (T2) in 2011. At T1, 2,809 employees responded (68% response rate), and at T2, 3,202 employees responded (66% response rate). Analyses included descriptive statistics and logistic regression. An open-ended question was also included and analyzed using content analysis.ResultsBullying prevalence remained quite stable between T1 and T2. At both time points, women and lecturers reported slightly higher rates of being targets of bullying compared to men and other academic positions. Moreover, 25% of employees reporting bullying at T1 had left the university by T2, and the response rate among those still employed but previously bullied was lower than the total population. Of those bullied at T1, only 34% reported continued bullying at T2, with 119 new cases identified at T2. Sex differences emerged, with women often experiencing sex-related bullying and men encountering ethnicity-related bullying. Managers and co-workers were identified as the primary perpetrators, with women more likely than men to report students as bullies. Key bullying causes included relational conflicts, communication issues, and power imbalances intensified by academia’s hierarchical structure.ConclusionBullying remains a significant issue in academia, influenced by competitive and hierarchical institutional structures that reinforce power dynamics. Whilst overall prevalence appears stable, underlying shifts, such as turnover among those previously bullied and new instances emerging, reveal a complex and evolving problem. Sex-specific patterns in bullying experiences underscore the importance of tailored interventions. These findings highlight the need for structured, institutional interventions in academia to address and mitigate bullying, ultimately fostering a healthier work environment.